CtDNA MRD Detection and Personalized Oncogenomic Analysis in Oligometastatic Colorectal Cancer From Plasma and Urine. (December 2021) - Pellini, Bruna; Pejovic, Nadja; Feng, Wenjia; Earland, Noah; Harris, Peter K.; Usmani, Abul; Szymanski, Jeffrey J.; Qaium, Faridi; Mudd, Jacqueline; Petty, Marvin; Jiang, Yuqiu; Singh, Ashla; et al.
Abstract : PURPOSE : We hypothesized that circulating tumor DNA (ctDNA) molecular residual disease (MRD) analysis without prior mutational knowledge could be performed after neoadjuvant chemotherapy to assess oligometastatic colorectal cancer (CRC) treated surgically with curative intent. We also investigated urine as an alternative analyte for ctDNA MRD detection in this nongenitourinary setting. PATIENTS AND METHODS : We applied AVENIO targeted next‐generation sequencing to plasma, tumor, and urine samples acquired on the day of curative‐intent surgery from 24 prospectively enrolled patients with oligometastatic CRC. Age‐related clonal hematopoiesis was accounted for by removing variants also present in white blood cells. Plasma and urine ctDNA MRD were correlated with tumor cells detected in the surgical specimen, and adjuvant treatment strategies were proposed based on ctDNA‐inferred tumor mutational burden (iTMB) and targetable alterations. RESULTS : Seventy‐one percent of patients were treated with neoadjuvant chemotherapy. Tumor‐naive plasma ctDNA analysis detected MRD at a median level of 0.62% with 95% sensitivity and 100% specificity, and 94% and 77% sensitivity when only considering patients treated with neoadjuvant chemotherapy and putative driver mutations, respectively. In urine, ctDNA MRD detection specificity remained high at 100%, but sensitivity decreased to 64% with median levels being 11‐fold lower than in plasma ( P < .0001). Personalized ctDNA MRD oncogenomic analysis revealed 81% of patients might have been candidates for adjuvant immunotherapy based on high iTMB or targeted therapy based on actionable PIK3CA mutations. CONCLUSION : Tumor‐naive plasma ctDNA analysis can sensitively and specifically detect MRD in patients with oligometastatic CRC after neoadjuvant chemotherapy. Urine‐based ctDNA MRD detection is also feasible; however, it is less sensitive than plasma because of significantly lower levels. Oligometastatic patients with detectable MRD may benefit from additional personalized treatment based on ctDNA‐derived oncogenomic profiling.